Analysis of Landslide Hazard Vulnerability Level in Hukuanakota Village, Inamoso District, West Seram Regency - Kapitan, Novita; Leuwol, Ferdinand Salomo; Riry, Roberth Berthy (JENDELA PENGETAHUAN, 2025)
This study aims to assess the landslide susceptibility of Hukuanakota Village, located in Inamosol District, Seram Bagian Barat Regency, by analyzing various environmental and physical parameters. The parameters examined include slope gradient, rainfall, soil texture, soil permeability, effective soil depth, groundwater depth, vegetation density, previous landslide events, and land use. Utilizing Geographic Information System (GIS) technology, this research successfully developed a landslide susceptibility zoning map, categorized into four levels: low, moderate, high, and very high. The findings reveal that areas with low susceptibility are generally located in flat regions with stable land use, such as settlements and paddy fields, while areas with very high susceptibility are concentrated in steep slopes with high rainfall, poor vegetation cover, and previous landslide occurrences. The study also emphasizes the importance of mitigating strategies such as vegetation planting, the creation of drainage systems, and routine monitoring of soil and slope conditions. The landslide susceptibility map serves as a valuable tool for local governments and communities, providing essential information for land use planning, disaster risk reduction, and improving preparedness against future landslide disasters. With the map’s aid, more effective and targeted mitigation measures can be implemented to reduce the impact of landslides and enhance the community's resilience to natural disasters.